1988
DOI: 10.1351/pac198860070959
|View full text |Cite
|
Sign up to set email alerts
|

Solution photochemistry of poly(dialkylsilanes): a new class of photoresists

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 0 publications
1
32
1
Order By: Relevance
“…The visible emissions of polysilanes have been widely investigated. The origins of visible emission have been attributed to (1) branch of silicon backbone [11], (2) -* charge transfer transition [12,13], (3) photolysis product [14] or (4) extrinsic impurity emission [15]. The steric hindrance of the alkoxyl groups affected the emission behaviors.…”
Section: Oxygen-crosslinkingmentioning
confidence: 99%
“…The visible emissions of polysilanes have been widely investigated. The origins of visible emission have been attributed to (1) branch of silicon backbone [11], (2) -* charge transfer transition [12,13], (3) photolysis product [14] or (4) extrinsic impurity emission [15]. The steric hindrance of the alkoxyl groups affected the emission behaviors.…”
Section: Oxygen-crosslinkingmentioning
confidence: 99%
“…Early semiempirical and ab initio calculations suggested that these σ→σ* excitation energies are highly dependent on the backbone conformation along the Si−Si chain 11, 12. For example, the striking thermochromism of polysilane solutions, namely the bathochromic shift of the absorption in the near UV upon cooling, has been attributed to the increase of the relative population of all‐ trans segments at lower temperatures 10, 13, 14. Recent research focused primarily on tetrasilanes, which are the simplest oligosilanes that offer backbone conformations.…”
mentioning
confidence: 99%
“…[24,26,28] The short radiative lifetimes, narrow spectral band width, and lack of fine structure of the fluorescence is suggestive of a highly delocalized excited state. Comparison of the absorption and emission spectra of poly(di-n-hexylsilane) in solution suggests that emission is occurring from segments containing 20-36 silicon atoms, assuming that the oscillator strength is independent of the chromophore length.…”
Section: Advanced M Aterl Alsmentioning
confidence: 99%